BASIC CONCEPTS OF ACCOUNTING IN ISLAMIC PERSPECTIVE - Hasina , Tazkiya; Sulastiningsih , Sulastiningsih; Mada, Puteh-o (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The current form of conventional accounting has been influenced and shaped by the prevailing value system present in Western civilization. Hence, it is indisputable that the conceptual framework employed as the foundation for formulating and advancing accounting rules exhibits a bias towards specific interest groups. Can the conceptual framework be used to accounting practices based on Sharia principles? This research posits that Islam possesses distinct values that diverge from the prevailing ideals that underpin the establishment and advancement of traditional accounting practices. Hence, it is imperative to critically evaluate the utilization of Western accounting in its current state. This paper presents a comprehensive examination of the conceptual framework of conventional accounting, while also discussing the conceptual framework of financial reporting from an Islamic standpoint. This discussion encompasses the notion of responsibility as it pertains to financial statements, the underlying objectives of financial statements, the qualitative attributes of information contained therein, and the constituent elements comprising financial statements. This composition is grounded in the use of logical reasoning derived from the primary source of Islamic jurisprudence, specifically the Qur'an.